(3cJGH aj GdUdGI Ydi GdfHj Udi Gddg Ydjg hSdes - (3eLghds
(3ChdgG (B:s
(3Gddge Ud hSde Ydi SjOfG hehdGfG eMeO hYdi Bd SjOfG eMeO GdPj OYG Cf jLjH Gddg CHG gQjQI hCeI GdeDefjf hcGf aj GdCfGes
(3BNQgG (B:s
(3GSJXd JMJ dhGFg hNHGHg hONd aj Ojf Gddg ef HGHg Udi Gddg Ydjg hYdi Cdg hCUMGHgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs